Phthalocyanine material with core-shell structure as well as preparation method and application of phthalocyanine material

By designing a phthalocyanine material with a core-shell structure, using β-phthalocyanine as the shell material and the silicon dioxide core, the problem of lack of margin warning for the battery separator is solved, and the efficient use of the separator and good electrochemical performance are achieved.

CN119695395APending Publication Date: 2025-03-25福建龙净储能电池有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411869301.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing battery diaphragm lacks the residual warning treatment, which leads to an increase in unforeseen losses during use, making it difficult to control, and it is easy to cause half of the diaphragm to be assembled in the core, resulting in scrapping of positive and negative electrode sheets.

Method used

A phthalocyanine material with a core-shell structure was designed. A cell separator with excellent performance was prepared by β-phthalocyanine as the shell material and combined with the silicon dioxide core. By controlling the shell thickness, an early warning of the remaining amount of the separator is achieved.

Benefits of technology

The margin warning function of the battery separator is realized, avoiding the waste of positive and negative electrode sheets, and the battery composite separator has good electrochemical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695395A_ABST
    Figure CN119695395A_ABST
Patent Text Reader

Abstract

The invention provides a phthalocyanine material with a core-shell structure as well as a preparation method and application of the phthalocyanine material. The core of the phthalocyanine material with the core-shell structure comprises silicon dioxide, and the material of the shell layer comprises beta-phthalocyanine complexed with nonferrous metal ions. The preparation method comprises the following steps: mixing silicon dioxide, a catalyst A, a modifier and a solvent, and carrying out surface modification to obtain modified silicon dioxide; adding a phthalic anhydride compound and a nitrogen-containing compound, and reacting to obtain ammoniated modified silicon dioxide; adding a metal salt and a catalyst B, reacting, and carrying out cold pickling and water washing to obtain a phthalocyanine material with a core-shell structure; the temperature of cold pickling is less than or equal to 20 DEG C. By designing the phthalocyanine material with the core-shell structure, the material which is excellent in performance and can be used for preparing the battery diaphragm capable of providing residual early warning is prepared, and the battery composite diaphragm prepared from the material has relatively good electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery separators, and in particular relates to a phthalocyanine material with a core-shell structure and a preparation method and application thereof. Background Art

[0002] As the scale of the new energy industry grows and the industrial chain gradually improves, cost has become a key weapon for major battery manufacturers to compete, so cost control is particularly important. The diaphragm is one of the core components of lithium-ion batteries, and its utilization rate is related to the yield of the entire manufacturing process. At present, there is no corresponding reserve warning treatment for the diaphragm in the industry, resulting in unpredictable remaining amount at the bottom of each roll of diaphragm tube. Even if the length of each roll of diaphragm remains the same, the unforeseen loss during use will increase the difficulty of control. There is a high probability that half of the diaphragm will not be enough for the core assembly, and the positive and negative electrodes cannot be reworked and reused and can only be scrapped. A 280Ah battery cell pulling line can change the diaphragm roll more than 200 times in a single shift. The above phenomenon will occur every time the roll is changed, which is equivalent to scrapping 100ea batteries.

[0003] Therefore, how to provide a material that can be used to prepare battery separators, can provide early warning of the remaining amount of the separator, and has excellent performance has become a technical problem that needs to be solved urgently. Summary of the invention

[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a phthalocyanine material with a core-shell structure and a preparation method and application thereof. The present invention designs a phthalocyanine material with a core-shell structure and further uses β-phthalocyanine as a shell material to prepare a material with excellent performance that can be used to prepare a battery separator that can provide a surplus warning, and the battery composite separator prepared thereby has good electrochemical properties.

[0005] To achieve this object, the present invention adopts the following technical solutions:

[0006] In a first aspect, the present invention provides a phthalocyanine material with a core-shell structure, wherein the core of the phthalocyanine material with a core-shell structure comprises silicon dioxide, and the material of the shell layer comprises β-phthalocyanine complexed with a non-ferrous metal ion;

[0007] The thickness of the shell layer is 20 nm to 300 nm, for example, it can be 20 nm, 40 nm, 60 nm, 80 nm, 100 nm, 120 nm, 150 nm, 180 nm, 200 nm, 230 nm, 250 nm, 270 nm or 300 nm.

[0008] The present invention designs a phthalocyanine material with a core-shell structure and further uses β-phthalocyanine as a shell material to prepare a material with excellent performance that can be used to prepare a battery separator that can provide a surplus warning. The battery composite separator prepared in this way has good electrochemical properties.

[0009] Phthalocyanine It is a macrocyclic compound with a large π system of 18 π electrons. Its special conjugated structure makes it have relatively stable chemical properties. The active hydrogen on the two amino groups of free phthalocyanine is not replaced, and various metal complexes can be prepared by modification. These complexes have bright colors and strong coloring power. The bright colors of phthalocyanine materials can be easily recognized by CCD (automatic recognition by visual automated detection equipment), but ordinary phthalocyanine is in contact with positive and negative electrodes for a long time, and the π-π structure is easily dissociated after long-term electrochemical reaction, resulting in deterioration of electrolyte decomposition. In the present invention, β-phthalocyanine ( M represents non-ferrous metal ions, such as Cu 2+ The shell material can reduce the decomposition and deterioration of the electrolyte, and the battery separator prepared thereby has good electrochemical properties.

[0010] In the present invention, the silicon dioxide core provides a growth interface for phthalocyanine, so that under the same chromaticity, the phthalocyanine material with a core-shell structure provided by the present invention has a smaller proportion of phthalocyanine. At the same time, phthalocyanine is converted into β-phthalocyanine with a more stable crystal form after cold treatment, which has less side effects on the battery. The silicon dioxide core can react with HF. 2 Making the core can reduce the concentration of HF in the electrolyte.

[0011] In the present invention, by controlling the thickness of the shell layer within a specific range, the phthalocyanine material with a core-shell structure is ensured to have a bright color, and can be set as an early warning material on one side of the diaphragm to obtain a composite diaphragm, the color of which can be easily identified by the CCD, providing an early warning of the remaining amount of the diaphragm, and avoiding waste of positive and negative electrodes. If the thickness of the shell layer is too low, the color of the phthalocyanine material with a core-shell structure is too light, and it is difficult to provide an effective early warning of the remaining amount of the composite diaphragm; if the thickness of the shell layer is too high, it will have an adverse effect on the electrical performance of the battery.

[0012] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0013] As a preferred technical solution of the present invention, the D of the silicon dioxide 50The particle size is 50 nm to 5 μm, for example, it can be 50 nm, 100 nm, 200 nm, 400 nm, 600 nm, 800 nm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm.

[0014] Preferably, the specific surface area of ​​the silicon dioxide is 200 m 2 / g~600m 2 / g, for example, it can be 200m 2 / g, 250m 2 / g、300m 2 / g, 350m 2 / g, 400m 2 / g, 450m 2 / g、500m 2 / g, 550m 2 / g or 600m 2 / g, etc.

[0015] As a preferred technical solution of the present invention, the raw materials for preparing the phthalocyanine material with a core-shell structure include the following components in parts by weight:

[0016]

[0017]

[0018] In the present invention, by controlling the amount of catalyst A within a specific range, a phthalocyanine material with a core-shell structure having a shell layer of suitable thickness can be prepared. If the amount of the catalyst is too small, the shell layer of the phthalocyanine material with a core-shell structure is too thin; if the amount of the catalyst is too large, the thickness of the shell layer of the phthalocyanine material with a core-shell structure will not be increased, but will cause a waste of raw materials.

[0019] At the same time, the present invention can prepare a phthalocyanine material with a core-shell structure and a shell layer with a suitable thickness by controlling the amount of the phthalic anhydride compound and the nitrogen-containing compound within a specific range. If the amount of the phthalic anhydride compound and the nitrogen-containing compound is too small, the shell layer of the phthalocyanine material with a core-shell structure is too thin; if the amount of the phthalic anhydride compound and the nitrogen-containing compound is too large, the shell layer of the phthalocyanine material with a core-shell structure is too thick, which will have an adverse effect on the electrical properties of the battery during subsequent use.

[0020] In the present invention, the weight proportion of silicon dioxide in the raw material for preparing the phthalocyanine material with a core-shell structure can be 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts or 35 parts, etc.

[0021] The weight proportion of catalyst A in the raw material for preparing the core-shell phthalocyanine material can be 1 part, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, 2 parts, 2.2 parts, 2.4 parts, 2.6 parts, 2.8 parts or 3 parts, etc.

[0022] The weight proportion of catalyst B in the raw material for preparing the core-shell phthalocyanine material can be 1 part, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, 2 parts, 2.2 parts, 2.4 parts, 2.6 parts, 2.8 parts or 3 parts, etc.

[0023] The weight proportion of the modifier in the raw material for preparing the phthalocyanine material with a core-shell structure can be 4 parts, 4.2 parts, 4.4 parts, 4.6 parts, 4.8 parts, 5 parts, 5.2 parts, 5.4 parts, 5.6 parts, 5.8 parts or 6 parts, etc.

[0024] The weight proportion of phthalic anhydride compounds in the raw materials for preparing the core-shell phthalocyanine material can be 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts or 18 parts, etc.

[0025] The weight proportions of the nitrogen-containing compound in the raw materials for preparing the phthalocyanine material with a core-shell structure can be 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, 8.5 parts, 9 parts, 9.5 parts, 10 parts, 10.5 parts, 11 parts, 11.5 parts or 12 parts, etc.

[0026] The weight proportions of the metal salt in the raw materials for preparing the core-shell phthalocyanine material can be 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts or 8 parts, etc.

[0027] As a preferred technical solution of the present invention, the catalyst is selected from any one of molybdic acid, ammonium molybdate or bismuth molybdate, or a combination of at least two thereof.

[0028] Preferably, the modifying agent comprises a surfactant.

[0029] Preferably, the cationic surfactant comprises a quaternary ammonium salt cationic surfactant, and more preferably the cationic surfactant is selected from any one or a combination of at least two of cetyltrimethylammonium bromide (CTAB), dodecyldimethylamine oxide or octadecyldimethylbenzyl quaternary ammonium chloride.

[0030] Preferably, the phthalic anhydride compound is selected from any one of phthalic acid, phthalic anhydride or 3.5-dimethylphthalic anhydride, or a combination of at least two thereof.

[0031] Preferably, the nitrogen-containing compound is selected from any one or a combination of at least two of urea, formamide or acetamide, and more preferably urea.

[0032] Preferably, the metal salt includes any one of ferric chloride, cupric chloride, ferric nitrate or chromium sulfate, or a combination of at least two thereof.

[0033] In a second aspect, the present invention provides a method for preparing the phthalocyanine material having a core-shell structure as described in the first aspect, the preparation method comprising the following steps:

[0034] (1) performing surface modification treatment on silicon dioxide: mixing silicon dioxide, catalyst A, a modifier and a solvent, and performing a modification reaction to obtain modified silicon dioxide;

[0035] (2) Ammoniation of benzoic acid ester: adding phthalic anhydride compound and nitrogen-containing compound to the reaction system obtained in step (1) to react and obtain ammoniation-modified silica;

[0036] (3) Preparation of a phthalocyanine material with a core-shell structure: adding a metal salt and a catalyst B to the reaction system obtained in step (2), reacting, and then cold acid washing and water washing to obtain the phthalocyanine material with a core-shell structure;

[0037] During the cold pickling, the temperature of the cold acid is ≤20°C.

[0038] The present invention utilizes the weak alkalinity of the silicon dioxide surface to make the catalyst adsorb to the surface layer and pores of the silicon dioxide. Meanwhile, the modifier is adsorbed on the silicon dioxide surface to modify the charge on its surface, so as to facilitate the subsequent guidance of phthalic anhydride compounds and nitrogen-containing compounds to perform an aminating reaction on the silicon dioxide surface. Meanwhile, the present invention is designed to add catalyst A in step (1) to catalyze the phthalic anhydride compounds and nitrogen-containing compounds to perform an aminating reaction on the silicon dioxide surface, so as to facilitate the formation of the subsequent phthalocyanine coating layer. If catalyst A is added in step (2), the phthalic anhydride compounds and nitrogen-containing compounds will react directly in the reaction system, rather than reacting preferentially on the silicon dioxide surface, which will eventually lead to the failure to form a phthalocyanine coating layer of suitable thickness on the silicon dioxide surface, and even to the difficulty of forming a continuous phthalocyanine coating layer on the silicon dioxide surface.

[0039] In the present invention, the phthalic anhydride compound and the nitrogen-containing compound in step (2) undergo an amination reaction under the action of the catalyst A in step (1) to obtain an amino-containing compound, which is adsorbed on the surface of the silica to obtain an ammoniated modified silica. In step (3), the amino-containing compound undergoes a condensation reaction under the action of the catalyst B to form a phthalocyanine coating layer, and the cations in the metal salt are complexed with the phthalocyanine to obtain a brightly colored coating layer.

[0040] In the present invention, the in-situ grown phthalocyanine is transformed into β-phthalocyanine with stable crystal form by cold acid washing, and the cold acid washing can also remove the excess acid anhydride and unreacted enzyme, and then the phthalocyanine is washed with deionized water until it is neutral.

[0041] In the present invention, the temperature of the cold acid is ≤20°C, for example, it can be 5°C, 6°C, 7°C, 8°C, 9°C, 10°C, 11°C, 12°C, 13°C, 14°C, 15°C, 16°C, 17°C, 18°C, 19°C or 20°C, etc.

[0042] As a preferred technical solution of the present invention, the solvent is selected from an organic solvent with a boiling point ≥200°C (for example, it can be 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C or 300°C, etc.).

[0043] Preferably, the solvent is selected from trichlorotoluene and / or diphenyl ether.

[0044] Preferably, the mixing method in step (1) comprises: stirring and mixing the silica and the aqueous solution of the catalyst at 20°C to 30°C (for example, 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C or 30°C, etc.) for 5min to 15min (for example, 5min, 6min, 7min, 8min, 9min, 10min, 11min, 12min, 13min, 14min or 15min, etc.), filtering out for standby use, and obtaining silica adsorbed with the catalyst;

[0045] After the modifier and the solvent are mixed, the silica adsorbed with the catalyst is added thereto and mixed for 5 min to 15 min (for example, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min or 15 min, etc.);

[0046] Alternatively, at 20°C to 30°C (for example, 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C or 30°C, etc.), stir and mix silica, a catalyst and a solvent for 10-30 minutes (10 minutes, 12 minutes, 14 minutes, 16 minutes, 18 minutes, 20 minutes, 22 minutes, 24 minutes, 26 minutes, 28 minutes or 30 minutes, etc.), and then add a modifier and mix.

[0047] It should be noted that the mass percentage of the catalyst in the aqueous solution of the catalyst is 3-6%, for example, it can be 3%, 3.3%, 3.6%, 3.9%, 4.2%, 4.5%, 4.8%, 5%, 5.2%, 5.5%, 5.7% or 6%.

[0048] Preferably, the ratio between the mass of the modifier and the volume of the solvent is 1g:(35-45)mL, for example, it can be 1g:35mL, 1g:36mL, 1g:37mL, 1g:38mL, 1g:39mL, 1g:40mL, 1g:41mL, 1g:42mL, 1g:43mL, 1g:44mL or 1g:35mL, etc.

[0049] Preferably, the temperature of the modification reaction in step (1) is 20°C to 30°C (for example, it can be 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C or 30°C, etc.), and the time is 10min to 30min (for example, it can be 10min, 12min, 14min, 16min, 18min, 20min, 22min, 24min, 26min, 28min or 30min, etc.).

[0050] As a preferred technical solution of the present invention, the reaction temperature in step (2) is 100°C to 130°C (for example, it can be 100°C, 102°C, 105°C, 108°C, 110°C, 112°C, 115°C, 117°C, 120°C, 121°C, 124°C, 127°C or 130°C, etc.), and the reaction time is 1h to 4h (for example, it can be 1h, 1.5h, 2h, 2.5h, 3h, 3.5h or 4h, etc.).

[0051] Preferably, the temperature of the condensation reaction in step (3) is 200°C to 260°C (for example, it can be 220°C, 225°C, 230°C, 235°C, 240°C, 245°C, 250°C, 255°C or 260°C, etc.), and the time is 1h to 3h (for example, it can be 1h, 1.5h, 2h, 2.5h or 3h, etc.).

[0052] Preferably, the acid used for the cold pickling comprises hydrochloric acid and / or hydrofluoric acid.

[0053] Preferably, the concentration of the hydrochloric acid is 0.5wt% to 2wt%, for example, it can be 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt% or 2wt%, etc.

[0054] Preferably, a post-treatment step is further included after the water washing, and the post-treatment method includes: drying and ball milling.

[0055] In the present invention, ball milling is used to facilitate subsequent arrangement with one side of the diaphragm to form a composite diaphragm,

[0056] As a preferred technical solution of the present invention, the preparation method comprises the following steps:

[0057] (1) performing surface modification treatment on silicon dioxide: mixing silicon dioxide, catalyst A, a modifier and a solvent, and performing surface modification at 20° C. to 30° C. for 10 min to 30 min to obtain modified silicon dioxide;

[0058] (2) Amination of benzoic acid ester: Add phthalic anhydride compounds and nitrogen-containing compounds to the reaction system obtained in step (1), react at 100° C. to 130° C. for 1 h to 4 h to obtain aminated modified silica;

[0059] (3) Preparation of a phthalocyanine material with a core-shell structure: adding a metal salt to the reaction system obtained in step (2), reacting at 200° C. to 260° C. for 1 h to 3 h, then cold acid washing and water washing, drying, and ball milling to obtain the phthalocyanine material with a core-shell structure;

[0060] During the cold pickling, the temperature of the cold acid is ≤20°C.

[0061] In a third aspect, the present invention provides an application of the phthalocyanine material with a core-shell structure as described in the first aspect, wherein the phthalocyanine material with a core-shell structure is used to prepare a composite diaphragm;

[0062] Preferably, the composite separator is used as a battery separator.

[0063] Preferably, the composite membrane comprises a phthalocyanine material layer having a core-shell structure and a membrane.

[0064] In the present invention, there is no special limitation on the preparation method of the composite diaphragm, and all commonly used preparation methods in the art are applicable, including but not limited to: disposing a phthalocyanine material having a core-shell structure on one side of the diaphragm by printing or coating to obtain the composite diaphragm.

[0065] It should also be noted that the present invention does not have any special restrictions on the thickness of the phthalocyanine material layer with a core-shell structure, and the commonly used thickness ranges in the field are applicable, including but not limited to: 20nm to 300nm, for example, it can be 20nm, 40nm, 60nm, 80nm, 100nm, 120nm, 150nm, 180nm, 200nm, 230nm, 250nm, 270nm or 300nm, etc.

[0066] The composite diaphragm provided by the present invention can be detected by CCD to identify the remaining amount of the composite diaphragm in advance, thereby avoiding the problem of pole piece waste due to insufficient composite diaphragm during the core manufacturing process.

[0067] Compared with the prior art, the present invention has the following beneficial effects:

[0068] The present invention designs a phthalocyanine material with a core-shell structure, further uses β-phthalocyanine as a shell material, and prepares a material with excellent performance that can be used to prepare a battery separator. The prepared battery separator has good electrochemical properties. The thickness of the shell material in the prepared phthalocyanine material with a core-shell structure is 132nm-175nm, the L value in Lab is 40.1-41.2, the a value is 6.3-8.7, and the b value is -12.3--35.4. BRIEF DESCRIPTION OF THE DRAWINGS

[0069] Figure 1 It is a schematic structural diagram of the phthalocyanine material with a core-shell structure provided in Example 1 of the present invention.

[0070] Figure 2 1 is the XRD spectrum of the phthalocyanine material with a core-shell structure obtained before and after cold pickling in step (3) of Example 1 of the present invention. DETAILED DESCRIPTION

[0071] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0072] The sources of some components in the embodiments and comparative examples are as follows:

[0073] Silica: Aladdin, S433685, D 50 3μm, specific surface area 260m 2 / g.

[0074] Example 1

[0075] This embodiment provides a phthalocyanine material with a core-shell structure and a preparation method thereof. The core of the phthalocyanine material with a core-shell structure includes silicon dioxide, and the material of the shell layer includes β-phthalocyanine complexed with a non-ferrous metal ion (the non-ferrous metal ion is Cu 2+ );

[0076] The preparation method of the above-mentioned phthalocyanine material with core-shell structure is as follows:

[0077] (1) At 25° C., silica (30 g) and an aqueous solution of ammonium molybdate (the mass percentage of ammonium molybdate is 5%, and the mass of ammonium molybdate is 2 g) are stirred and mixed for 10 min, and then filtered out for later use to obtain silica adsorbing ammonium molybdate;

[0078] After CTAB (5 g) and trichlorotoluene (200 mL) were mixed, silica adsorbed with ammonium molybdate was added thereto, and surface modification was performed by ultrasonic dispersion at 25° C. for 15 min to obtain modified silica;

[0079] (2) Amination of benzoic acid ester: Add 3,5-dimethylphthalic anhydride (15 g) and urea (8 g) to the reaction system obtained in step (1), and react at 120° C. for 1 h to obtain ammoniation-modified silica;

[0080] (3) Preparation of phthalocyanine material with core-shell structure: copper chloride (5 g) and molybdic acid (3 g) were added to the reaction system obtained in step (2), and the mixture was reacted at 240°C for 2 h. The mixture was then cold-picked with 1% hydrochloric acid at 10°C, washed with deionized water until neutral (pH = 7), dried, and ball-milled at 200 rpm for 30 min (using large, medium and small grinding beads with a radius ratio of 1:0.5:0.2 (the radius of the small grinding beads was 2 mm), and the weight ratio of the three grinding beads was 8%:82%:10%) to obtain the phthalocyanine material with core-shell structure.

[0081] The phthalocyanine material with a core-shell structure obtained before and after cold pickling in step (3) of this embodiment was characterized, and its XRD spectrum is as follows: Figure 2 As shown. Figure 2 It can be seen that the present invention transforms the in-situ grown phthalocyanine into β-phthalocyanine with stable crystal form through cold acid washing.

[0082] Example 2

[0083] This embodiment provides a phthalocyanine material with a core-shell structure and a preparation method thereof. The core of the phthalocyanine material with a core-shell structure includes silicon dioxide, and the material of the shell layer includes β-phthalocyanine complexed with a non-ferrous metal ion (the non-ferrous metal ion is Cu 2+ );

[0084] The preparation method of the above-mentioned phthalocyanine material with core-shell structure is as follows:

[0085] (1) At 25° C., silica (25 g) and an aqueous solution of ammonium molybdate (the mass percentage of ammonium molybdate is 5%, and the mass of ammonium molybdate is 1 g) are stirred and mixed for 10 min, and then filtered out for later use to obtain silica adsorbing ammonium molybdate;

[0086] After CTAB (4 g) and trichlorotoluene (140 mL) were mixed, silica adsorbed with ammonium molybdate was added thereto, and surface modification was performed by ultrasonic dispersion at 25° C. for 5 min to obtain modified silica;

[0087] (2) Amination of benzoic acid ester: Add phthalic anhydride (15 g) and formamide (8 g) to the reaction system obtained in step (1), and react at 120° C. for 3 h to obtain aminated modified silica;

[0088] (3) Preparation of phthalocyanine material with core-shell structure: copper chloride (7 g) and ammonium molybdate (2 g) were added to the reaction system obtained in step (2), and the mixture was reacted at 240° C. for 2 h. The mixture was then cold-picked with 1% hydrochloric acid at 5° C., washed with deionized water until neutral (pH=7), dried, and ball-milled at 200 rpm for 30 min (using large, medium and small grinding beads with a radius ratio of 1:0.5:0.2 (the radius of the small grinding beads was 2 mm) to obtain the phthalocyanine material with core-shell structure.

[0089] Example 3

[0090] This embodiment provides a phthalocyanine material with a core-shell structure and a preparation method thereof. The core of the phthalocyanine material with a core-shell structure includes silicon dioxide, and the material of the shell layer includes β-phthalocyanine complexed with a non-ferrous metal ion (the non-ferrous metal ion is Fe 3+ );

[0091] The preparation method of the above-mentioned phthalocyanine material with core-shell structure is as follows:

[0092] (1) At 25° C., silicon dioxide (35 g), molybdic acid (3 g) and trichlorotoluene (240 mL, stirred for 5 min, ultrasonically dispersed for 5 min, with an ultrasonic power of 50 kHz, CTAB (6 g) was added thereto and ultrasonically dispersed at 25° C. for 15 min to perform surface modification, thereby obtaining modified silicon dioxide;

[0093] (2) Amination of benzoic acid ester: add phthalic acid (10 g) and acetamide (5 g) to the reaction system obtained in step (1), and react at 100° C. for 2 h to obtain aminated modified silica;

[0094] (3) Preparation of phthalocyanine material with core-shell structure: Add ferric chloride (3 g) and molybdic acid (3 g) to the reaction system obtained in step (2), react at 200° C. for 2 h, then cold pickle with 1% hydrochloric acid at 14° C., wash with deionized water until neutral (pH=7), dry, and ball mill at 200 rpm for 30 min (using large, medium and small grinding beads with a radius ratio of 1:0.5:0.2 (the radius of the small grinding beads is 2 mm) to obtain the phthalocyanine material with core-shell structure.

[0095] Example 4-Example 8, Comparative Example 1-Comparative Example 4

[0096] Embodiment 4 to Embodiment 8 and Comparative Examples 1 to Comparative Examples 4 respectively provide a phthalocyanine material with a core-shell structure and a preparation method thereof, wherein the core of the phthalocyanine material with a core-shell structure comprises silicon dioxide, and the material of the shell layer comprises β-phthalocyanine complexed with non-ferrous metal ions;

[0097] The specific selection and dosage of the raw materials for preparing the phthalocyanine material with a core-shell structure and the thickness of the shell layer are shown in Table 1 below.

[0098] The preparation method of the phthalocyanine material with a core-shell structure is as follows:

[0099] (1) At 25° C., silica and an aqueous solution of catalyst A (with a mass percentage of ammonium molybdate of 5%) were stirred and mixed for 10 minutes, and then filtered out for later use to obtain silica adsorbing ammonium molybdate;

[0100] After the modifier and the solvent are mixed, the silica adsorbing the catalyst A is added thereto, and the surface is modified by ultrasonic dispersion at 25° C. for 15 min to obtain modified silica;

[0101] (2) Amination of benzoic acid ester: adding phthalic anhydride compound and nitrogen-containing compound to the reaction system obtained in step (1), reacting at 120° C. for 60 min, to obtain aminated modified silica;

[0102] (3) Preparation of phthalocyanine material with core-shell structure: Add metal salt and catalyst B to the reaction system obtained in step (2), react at 240°C for 2h, use 1% hydrochloric acid for cold pickling, then use deionized water to wash to neutrality (pH=7), dry, and ball mill at 200 rpm for 30 min (using large, medium and small grinding beads with a radius ratio of 1:0.5:0.2 (the radius of the small grinding beads is 2 mm) to obtain the phthalocyanine material with core-shell structure;

[0103] The cold pickling temperature is shown in Table 1 below.

[0104] Table 1

[0105]

[0106] Comparative Example 5

[0107] This comparative example provides a phthalocyanine material with a core-shell structure and a preparation method thereof, wherein the core of the phthalocyanine material with a core-shell structure comprises silicon dioxide, and the material of the shell layer comprises β-phthalocyanine complexed with non-ferrous metal ions;

[0108] The preparation method of the above-mentioned phthalocyanine material with core-shell structure is as follows:

[0109] (1) At 25° C., silica (30 g), CTAB (5 g) and trichlorotoluene (200 mL) were stirred and mixed for 5 min, and surface modified by ultrasonic dispersion at 25° C. for 15 min to obtain modified silica;

[0110] (2) Amination of benzoic acid ester: Add 3,5-dimethylphthalic anhydride (15 g), urea (8 g) and ammonium molybdate (2 g) to the reaction system obtained in step (1), and react at 120° C. for 60 min to obtain ammoniation-modified silica;

[0111] (3) Preparation of phthalocyanine material with core-shell structure: copper chloride (5 g) and molybdic acid (3 g) were added to the reaction system obtained in step (2), and the mixture was reacted at 240° C. for 2 h. The mixture was then cold-picked with 1% hydrochloric acid at 10° C., washed with deionized water until neutral (pH=7), dried, and ball-milled at 200 rpm for 30 min (using large, medium and small grinding beads with a radius ratio of 1:0.5:0.2 (the radius of the small grinding beads was 2 mm) to obtain the phthalocyanine material with core-shell structure.

[0112] The performance of the phthalocyanine materials with a core-shell structure provided in the above examples and comparative examples was tested, and the specific testing method is as follows:

[0113] Shell thickness: Use a transmission electron microscope to test the shell thickness of phthalocyanine materials with a core-shell structure. Measure the shell thickness of 10 phthalocyanine materials with a core-shell structure and record the average value.

[0114] Lab: Tested using a spectrophotometer.

[0115] The above performance test results are shown in Table 2 below:

[0116] Table 2

[0117]

[0118] From the above content, it can be seen that the present invention designs a phthalocyanine material with a core-shell structure, further uses β-phthalocyanine as a shell material, and controls the thickness of the shell within a specific range, thereby preparing a material with excellent performance that can be used to prepare a battery separator, and the battery composite separator prepared in this way has good electrochemical properties. The thickness of the shell material in the prepared phthalocyanine material with a core-shell structure is 132nm~175nm, the L value in Lab is 40.1~41.2, the a value is 6.3~8.7, and the b value is -12.3~-35.4.

[0119] From the comparison between Examples 1-8 and Comparative Examples 1-5, it can be seen that if the amount of catalyst used in step (1) is too small (Comparative Example 1), or the amount of phthalic anhydride compounds and nitrogen-containing compounds used is too small (Comparative Example 2), or catalyst A is added in step (2) (Comparative Example 5), the β-phthalocyanine shell on the surface of silica will be too thin, and the color of the phthalocyanine material with a core-shell structure will be too light (a value or b value is low), making it difficult to provide an effective surplus warning for the remaining amount of the composite diaphragm; if the amount of phthalic anhydride compounds and nitrogen-containing compounds used is too large (Comparative Example 3), the β-phthalocyanine shell on the surface of silica will be too thick, and the composite diaphragm prepared in this way will have an adverse effect on the electrical properties of the battery during subsequent use.

[0120] From the comparison between Examples 1-8 and Comparative Example 4, it can be seen that the present invention prepares a β-phthalocyanine shell by controlling the temperature of cold pickling within a specific range, and the composite diaphragm prepared in this way has less side effects on the battery, and the silicon dioxide core can react with HF. 2 Making the core can reduce the concentration of HF in the electrolyte.

[0121] In summary, the present invention designs a phthalocyanine material with a core-shell structure, further uses β-phthalocyanine as the shell material, and controls the thickness of the shell within a specific range, thereby preparing a material with excellent performance that can be used to prepare a battery separator that can provide a surplus warning, and the battery composite separator prepared in this way has good electrochemical properties.

[0122] The applicant declares that the present invention uses the above embodiments to illustrate the detailed process flow of the present invention, but the present invention is not limited to the above detailed process flow, that is, it does not mean that the present invention must rely on the above detailed process flow to be implemented. Those skilled in the art should understand that any improvement to the present invention, equivalent replacement of the raw materials of the product of the present invention and auxiliary components.

Claims

1. A phthalocyanine material having a core-shell structure, characterized in that: The core of the phthalocyanine material with a core-shell structure includes silicon dioxide, and the material of the shell layer includes β-phthalocyanine complexed with colored metal ions; The thickness of the shell layer is 20nm to 300nm.

2. The phthalocyanine material with a core-shell structure according to claim 1, characterized in that: The D of the silica 50 Particle size is 50nm~5μm; Preferably, the specific surface area of ​​the silicon dioxide is 200 m 2 / g~600m 2 / g.

3. The phthalocyanine material with a core-shell structure according to claim 1 or 2, characterized in that: The raw materials for preparing the phthalocyanine material with a core-shell structure include the following components in parts by weight:

4. The phthalocyanine material with a core-shell structure according to claim 3, characterized in that: The catalyst A and catalyst B are each independently selected from any one or a combination of at least two of molybdic acid, ammonium molybdate or bismuth molybdate; Preferably, the modifier comprises a cationic surfactant; Preferably, the cationic surfactant comprises a quaternary ammonium salt cationic surfactant, and more preferably, the cationic surfactant is selected from any one or a combination of at least two of cetyltrimethylammonium bromide, dodecyldimethylamine oxide or octadecyldimethylbenzyl quaternary ammonium chloride.

5. The phthalocyanine material with a core-shell structure according to claim 3 or 4, characterized in that: The phthalic anhydride compound is selected from any one of phthalic acid, phthalic anhydride or 3.5-dimethylphthalic anhydride or a combination of at least two thereof; Preferably, the nitrogen-containing compound is selected from any one or a combination of at least two of urea, formamide or acetamide, and more preferably urea; Preferably, the metal salt includes any one of ferric chloride, cupric chloride, ferric nitrate or chromium sulfate, or a combination of at least two thereof.

6. A method for preparing the phthalocyanine material with a core-shell structure as claimed in any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: (1) performing surface modification treatment on silicon dioxide: mixing silicon dioxide, catalyst A, a modifier and a solvent, performing surface modification, and obtaining modified silicon dioxide; (2) Ammoniation of benzoic acid ester: adding phthalic anhydride compound and nitrogen-containing compound to the reaction system obtained in step (1) to react and obtain ammoniation-modified silica; (3) Preparation of a phthalocyanine material with a core-shell structure: adding a metal salt and a catalyst B to the reaction system obtained in step (2), reacting, and then cold acid washing and water washing to obtain the phthalocyanine material with a core-shell structure; During the cold pickling, the temperature of the cold acid is ≤20°C.

7. The preparation method according to claim 6, characterized in that: The solvent is selected from organic solvents with a boiling point ≥ 200°C; Preferably, the solvent comprises trichlorotoluene and / or diphenyl ether; Preferably, the ratio between the mass of the modifier and the volume of the solvent is 1 g: (35-45) mL; Preferably, the temperature of the modification reaction in step (1) is 20°C to 30°C, and the time is 10min to 30min.

8. The preparation method according to claim 6 or 7, characterized in that: The reaction temperature of step (2) is 100°C to 130°C, and the reaction time is 1h to 4h; Preferably, the reaction temperature in step (3) is 200°C to 260°C, and the reaction time is 1h to 3h; Preferably, the acid used for the cold pickling comprises hydrochloric acid and / or hydrofluoric acid; Preferably, a post-treatment step is further included after the water washing, and the post-treatment method includes: drying and ball milling.

9. The preparation method according to any one of claims 6 to 8, characterized in that: The preparation method comprises the following steps: (1) performing surface modification treatment on silicon dioxide: mixing silicon dioxide, catalyst A, a modifier and a solvent, and performing surface modification at 20° C. to 30° C. for 10 min to 30 min to obtain modified silicon dioxide; (2) Amination of benzoic acid ester: Add phthalic anhydride compounds and nitrogen-containing compounds to the reaction system obtained in step (1), react at 100° C. to 130° C. for 1 h to 4 h to obtain aminated modified silica; (3) Preparation of a phthalocyanine material with a core-shell structure: Add a metal salt and a catalyst B to the reaction system obtained in step (2), react at 200° C. to 260° C. for 1 h to 3 h, then perform cold acid washing and water washing, dry, and ball mill to obtain the phthalocyanine material with a core-shell structure; During the cold pickling, the temperature of the cold acid is ≤20°C.

10. Use of the phthalocyanine material with a core-shell structure as claimed in any one of claims 1 to 5, characterized in that: The phthalocyanine material with a core-shell structure is used to prepare a composite diaphragm; Preferably, the composite separator is used as a battery separator.